The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1364/josaa.16.002370
|View full text |Cite
|
Sign up to set email alerts
|

Predicting color from gray: the relationship between achromatic adjustment and asymmetric matching

Abstract: Achromatic adjustment has been used widely to study color context effects. In the achromatic adjustment procedure, an observer adjusts a test stimulus until it appears black, gray, or white. By its nature, achromatic adjustment directly measures the effect of context only for stimuli that appear gray. We present achromatic loci measured in two contexts and asymmetric color matches measured across the same two contexts. The results indicate that achromatic adjustments, together with a gain-control model, may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 23 publications
4
42
0
Order By: Relevance
“…In addition, categorical color constancy was as good for the chromatic as for the achromatic categories, with the exception of the black surfaces for which consistency was 100%. This is in agreement with Speigle and Brainard (1999), who showed that asymmetric matches for chromatic stimuli could be predicted from achromatic settings as long as the viewing conditions were held constant. Our data do point to a slight advantage for category prototypes in terms of classification consistency, but this issue needs to be investigated further with an experiment focused on category prototypes.…”
Section: Color Classification As a Methods For Measuring Color Constancysupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, categorical color constancy was as good for the chromatic as for the achromatic categories, with the exception of the black surfaces for which consistency was 100%. This is in agreement with Speigle and Brainard (1999), who showed that asymmetric matches for chromatic stimuli could be predicted from achromatic settings as long as the viewing conditions were held constant. Our data do point to a slight advantage for category prototypes in terms of classification consistency, but this issue needs to be investigated further with an experiment focused on category prototypes.…”
Section: Color Classification As a Methods For Measuring Color Constancysupporting
confidence: 92%
“…Such high constancy indices are in line with data collected for monitor simulations in full-field viewing conditions (Hansen et al, 2007;Murray et al, 2006;Olkkonen et al, 2009;Rinner & Gegenfurtner, 2000) and for achromatic settings for real stimuli (Speigle & Brainard, 1999) but are higher than indices reported for asymmetric matching experiments in either simulated or real scenes (e.g., Arend et al, 1991;Brainard et al, 1997).…”
Section: Color Constancy For the Achromatic Pointsupporting
confidence: 87%
“…Speigle and Brainard (1999) showed that measurements of what object appears achromatic under different illuminants may be used to predict how the appearance of othercolored objects will be affected across the same illumination changes.…”
Section: Methods Overviewmentioning
confidence: 99%
“…Although sometimes presented as measuring colour constancy, this method in fact provides data only on the appearance of neutral (i.e. greyscale) surfaces: indirect arguments can be made about its implications for asymmetric colour matching, but they require significant additional assumptions [38]. Insofar as subjects regard the method as adjusting surface colour, it effectively records their estimate of illuminant colour at that point in the scene (Figs.…”
Section: Judging Whitementioning
confidence: 99%